AN EDUCATIONAL ASSESSMENT OF PREVENTIVE BEHAVIORS OF CARDIOVASCULAR DISEASE AMONG ADULT WORKERS WITH HYPERTENSION - Markmee, Phataraphon; Wongwat, Rung (The Indonesian Journal of Public Health, 2024)
Introduction: In Thailand, approximately 13 million adult workers have hypertension, with approximately 4.7% of those living in acculturated societies at a higher risk of developing cardiovascular disease (CVD). Aims: This study aims to examine the factors that predicted CVD prevention behaviors in individuals with hypertension. Methods: A cross-sectional analytical study was conducted on 1,151 adult workers with hypertension from Sukhothai Province, Thailand, using a multistage sampling technique. The measurement tools included a standardized questionnaire approved by three experts and tested for reliability using the Cronbach's alpha. A multiple regression analysis was used to identify factors that predicted CVD prevention behaviors. Results: This study involved a total of 1,151 participants, 61.90% of whom were females, with an average age of 52 years. In addition, 71.80% of the participants had a family history of CVD. The majority of the participants (73.4%) exhibited moderate levels of CVD preventive behaviors. Factors that predicted CVD preventive behaviors included self-efficacy (β = 0.423), family and social support (β = 0.162), perceived information (β = 0.119), attitude (β = 0.117), knowledge (β = 0.089), living with nuisance (β = -0.049), and family history of hypertension (β = 0.049). These predictors accounted for 39.2% of the variance (R2 = 0.392, p = 0.05). Conclusion: The intervention mapping to promote CVD preventive behaviors in adult workers with hypertension should focus on increasing self-efficacy by providing information to improve individual knowledge and attitude, as well as addressing environmental factors that may affect people's well-being, such as nuisances.